Kenakalan Siswa SMK akibat Tekanan Keluarga melalui Pendekatan Konseling Humanistik - Donal; Salma Deyanti; Bening Muthmainnah SuryaNingsih Tambunan; Fajri Rivel (INDO PUBLISHING, 2026)
This study aims to describe the implementation of humanistic counseling in addressing delinquency among 12th-grade vocational students caused by family pressure. The research used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The results show that humanistic counseling: emphasizing empathy, unconditional positive regard, and genuineness, helped the student understand emotions, develop self-awareness, and improve behavior. After several sessions, the student showed positive changes such as reduced absenteeism and increased responsibility at school. The study concludes that humanistic counseling is effective in addressing student delinquency rooted in family pressure and highlights the importance of an empathetic and supportive counselor–client relationship.